Basic Principles of Information Technology Organization in Health Care Institutions - Mitchell, Joyce A. (American Medical Informatics Association, 1997)
This paper focuses on the basic principles of information technology (IT) organization within health sciences centers. The paper considers the placement of the leader of the IT effort within the health sciences administrative structure and the organization of the IT unit. A case study of the University of Missouri—Columbia Health Sciences Center demonstrates how a role-based organizational model for IT support can be effective for determining the boundary between centralized and decentralized organizations. The conclusions are that the IT leader needs to be positioned with other institutional leaders who are making strategic decisions, and that the internal IT structure needs to be a role-based hybrid of centralized and decentralized units. The IT leader needs to understand the mission of the organization and actively use change-management techniques.